2020
DOI: 10.1111/epi.16430
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy‐specific patient‐reported outcome measures of children's health‐related quality of life: A systematic review of measurement properties

Abstract: Objective To identify and appraise published evidence of the measurement properties for epilepsy‐specific patient‐reported outcome measures (PROMs) of children's health‐related quality of life (HRQoL). Methods We searched multiple databases for studies evaluating the measurement properties of English‐language epilepsy‐specific PROMs of children's HRQoL. We assessed the methodological quality using the COnsensus‐based Standards for the selection of health Measurement INstruments (COSMIN) guidance. We extracted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 54 publications
0
22
0
1
Order By: Relevance
“…This study is reported in line with the GRIPP2 short form for PPIE (supplementary 2) [ 53 ]. We consulted with a subset of members from our established Advisory Panel, consisting of children with epilepsy and parents, about the two leading candidate questionnaires from our systematic review [ 17 ], QOLCE-55 and CHEQOL. The members of our Advisory Panel responded to a call through national epilepsy charities and clinical services for people with experience of childhood epilepsy to join our Advisory Panel.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is reported in line with the GRIPP2 short form for PPIE (supplementary 2) [ 53 ]. We consulted with a subset of members from our established Advisory Panel, consisting of children with epilepsy and parents, about the two leading candidate questionnaires from our systematic review [ 17 ], QOLCE-55 and CHEQOL. The members of our Advisory Panel responded to a call through national epilepsy charities and clinical services for people with experience of childhood epilepsy to join our Advisory Panel.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, we focused on two leading candidate PROMs with better evidence of robust measurement properties from our prior systematic review [ 17 ]: Quality of Life in Childhood Epilepsy 55-item version (QOLCE-55) parent report and the Health-Related Quality of Life Measure for Children with Epilepsy (CHEQOL) child and parent report [ 18 , 19 ]. The QOLCE-55 is part of the QOLCE family of PROMs, which has four questionnaire versions with different numbers of items (QOLCE 76, QOLCE-55, QOLCE-16, and G-QOLCE) [ [19] , [20] , [21] , [22] , [23] , [24] , [25] ].…”
Section: Introductionmentioning
confidence: 99%
“…Several PROMs are now available for use in children with epilepsy, and, to guide decisions on choice of measures, there is an emerging literature evaluating the measures' robustness. 4 Such routine, standardized assess-ment of PROMs integrated into clinical care is a critical element in determining the quality of data collected, including the amount of attrition, which is essential to the success of longitudinal studies.…”
mentioning
confidence: 99%
“…2,3 Rosic and colleagues do us a great service by taking on this subject, not only in assessing depression, but by doing it repeatedly for 28 months. 4 The sample itself is impressive: 336 children and adolescents completed the study, although the group appeared to be largely heterogeneous.…”
mentioning
confidence: 99%
See 1 more Smart Citation